Environmental and Body Concentrations of Heavy Metals at Sites Near and Distant from Industrial Complexes in Ulsan, Korea - Sung, Joo Hyun; Oh, Inbo; Kim, Ahra; Lee, Jiho; Sim, Chang Sun; Yoo, Cheolin; Park, Sang Jin; Kim, Geun-Bae; Kim, Yangho (Journal of Korean medical science, 2018)
Industrial pollution may affect the heavy metal body burden of people living near industrial complexes. We determined the average concentrations of atmospheric heavy metals in areas close to and distant from industrial complexes in Korea, and the body concentrations of these heavy metals in residents living near and distant from these facilities. The atmospheric data of heavy metals (lead and cadmium) were from the Regional Air Monitoring Network in Ulsan. We recruited 1,148 participants, 872 who lived near an industrial complex ("exposed" group) and 276 who lived distant from industrial complexes ("non-exposed" group), and measured their concentrations of blood lead, urinary cadmium, and urinary total mercury. The results showed that atmospheric and human concentrations of heavy metals were higher in areas near industrial complexes. In addition, residents living near industrial complexes had higher individual and combined concentrations (cadmium + lead + mercury) of heavy metals. We conclude that residents living near industrial complexes are exposed to high concentrations of heavy metals, and should be carefully monitored.